2008
DOI: 10.1016/j.immuni.2008.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Crossreactive T Cells Spotlight the Germline Rules for αβ T Cell-Receptor Interactions with MHC Molecules

Abstract: To test whether highly crossreactive alphabeta T cell receptors (TCRs) produced during limited negative selection best illustrate evolutionarily conserved interactions between TCR and major histocompatibility complex (MHC) molecules, we solved the structures of three TCRs bound to the same MHC II peptide (IAb-3K). The TCRs had similar affinities for IAb-3K but varied from noncrossreactive to extremely crossreactive with other peptides and MHCs. Crossreactivity correlated with a shrinking, increasingly hydropho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
217
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(229 citation statements)
references
References 48 publications
12
217
0
Order By: Relevance
“…The germline-encoded V genes of the TCR are thought to determine bias toward the MHC (4,5), and consistent with this view there is evidence for preserved "interaction motifs" between the Vgene encoded regions of a TCR and a given MHC-II allotype (6,7). This has only been reported within a narrow slice of the Vβ repertoire, where consensus Vβ8.2 + CDR2β-mediated interactions were observed with closely related pMHC-II molecules (6,7).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The germline-encoded V genes of the TCR are thought to determine bias toward the MHC (4,5), and consistent with this view there is evidence for preserved "interaction motifs" between the Vgene encoded regions of a TCR and a given MHC-II allotype (6,7). This has only been reported within a narrow slice of the Vβ repertoire, where consensus Vβ8.2 + CDR2β-mediated interactions were observed with closely related pMHC-II molecules (6,7).…”
Section: Discussionmentioning
confidence: 79%
“…Nevertheless, conserved pairwise interactions between closely related Vβ8.2 + TCRs and pMHC-II molecules were identified, leading to the concept that there are defined interaction "motifs" or "codons" between the Vα and/or Vβ domains of a TCR and a given MHC allotype (3,(6)(7)(8). Central to the "interaction codon" hypothesis is that the CDR1 and CDR2 loops contact the MHC, whereas the CDR3 loops "read-out" the peptide leading to an inherent MHC bias of TCR recognition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent study focusing on the interaction of one particular Vb segment (Vb8.2) with different I-A MHC alleles has demonstrated the conservation of specific TCR-MHC interfacial contacts (12,13). A ''codon hypothesis'' which suggests that each TCR variable-region gene product engages each type of MHC through a ''menu'' of structurally coded recognition motifs that have arisen through coevolution has been proposed to clarify the existence of ''TCR-MHC bias'' or ''germlineencoded recognition'' of MHC.…”
Section: Specificity Determined By Interaction Of Ab T Cell Receptorsmentioning
confidence: 99%
“…Significant changes in TCR CDR3 loops can take place upon binding (57)(58)(59) and CDR3 can occupy different conformations depending upon which ligand is bound (60,61 mechanisms produced occur simul-taneously in the interface, not limited to molecular mimicry and CDR loop shifts (62). Recently, it has been reported that the cross-reactivity correlated with a shrinking, increasingly hydrophobic TCR-ligand interface (63), and a few conserved amino acids in CDR1 and CDR2 were involved in the engagement (63,64).…”
Section: Molecular Basis Of Mhc-i/tcr Interactionmentioning
confidence: 99%